2021
DOI: 10.12688/hrbopenres.13292.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceived barriers and enablers to fidelity of training and delivery of an intervention to reduce imaging for low back pain: a qualitative interview study protocol

Abstract: Background: Diagnostic imaging has limited utility in the assessment and management of non-specific low back pain (LBP), but remains commonly used in clinical practice. Interventions have been designed to reduce non-indicated imaging for LBP; however, evidence of effectiveness has been variable. It is unclear whether intervention fidelity was adequately assessed in these interventions, which may have an impact on the interpretation of trial results. Within implementation research, intervention fidelity refers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…This qualitative study was reported according to the COnsolidated criteria for Reporting Qualitative research (COREQ) checklist (Additional file 1 ). This study is part of a larger qualitative study that included multiple questions on enhancing and assessing fidelity to interventions to improve GP and chiropractor adherence to imaging guidelines for LBP; the full protocol and full interview guide for the larger study have been published [ 28 ]. The current study will focus on only the questions regarding the barriers and enablers to enhancing fidelity of training and delivery for these types of interventions.…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study was reported according to the COnsolidated criteria for Reporting Qualitative research (COREQ) checklist (Additional file 1 ). This study is part of a larger qualitative study that included multiple questions on enhancing and assessing fidelity to interventions to improve GP and chiropractor adherence to imaging guidelines for LBP; the full protocol and full interview guide for the larger study have been published [ 28 ]. The current study will focus on only the questions regarding the barriers and enablers to enhancing fidelity of training and delivery for these types of interventions.…”
Section: Methodsmentioning
confidence: 99%